The Effect of Sample Weigh, Incubation Duration And Isolation Methods on The Quality of Phalaeonopsis amabilis root DNA - Handayani, Etty; Rineksane, Innaka Ageng; Isnawan, Bambang Heri; Setiawan, Haris Anggita; Manto, Agus (Akademi Komunitas Perkebunan Yogyakarta, 2025)
Orchid Ph. amabilis is one of the plants designated as